Pengaruh Kompetensi, Integritas dan Independensi terhadap Opini Audit dengan Fee Audit sebagai Variabel Moderasii(Studii KasusiKantoriAkuntaniPubliki DiiKotaiMedan) - Zahra, Nur; Minan, Kersna; Nurmadi, Ruswan (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
This study aims to determine the effect of competence, integrity and independence on audit opinion with audit fees as a moderating variable at a public accounting firm in Medan. In this study using a saturated sampling method (census), which is a sampling method when all members of the population are sampled. The use of saturated sampling is because the entire population, namely 87 auditor samples, is the research sample. Of the 87 auditors at public accountants in the city of Medan, 47 samples were obtained that could be used as research data. The data used in this study is primary data in the form of a questionnaire using questions stated on a Likert scale of 1 to 5.The results of this study indicate that the competence and integrity variables have a significant effect on audit opinions at public accounting firms in Medan. Meanwhile, independence has no significant effect on audit opinion at a public accounting firm in Medan. Audit fees can moderate the ieffect iof competence iand iintegrity ion iaudit iopinions iat ipublic iaccounting ifirms iin Medan. iMeanwhile, ithe iaudit ifee icannot imoderate ithe iinfluence iof independence ion iaudit iopinion iin ithe icity iof iMedan.